2021
DOI: 10.51847/tifawab
|View full text |Cite
|
Sign up to set email alerts
|

Returning in‘new normal’– a thematic analysis of Twitter chat by pharmacy students

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…One of the limitations of our findings is that they are based on the students’ responses from one particular educational institute. However, similar experiences have been reported from pharmacy students across the country in other studies [ 24 , 27 ]. Moreover, although our study reported from the students’ perspective that their learning was negatively impacted by the shift to the online mode during the lockdown period, further exploration is necessitated to demonstrate the validity of this finding.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of the limitations of our findings is that they are based on the students’ responses from one particular educational institute. However, similar experiences have been reported from pharmacy students across the country in other studies [ 24 , 27 ]. Moreover, although our study reported from the students’ perspective that their learning was negatively impacted by the shift to the online mode during the lockdown period, further exploration is necessitated to demonstrate the validity of this finding.…”
Section: Discussionsupporting
confidence: 84%
“…At the time of writing, this pandemic is expected to last longer, affecting all walks of life. In the wake of this, one particular study with pharmacy students has suggested a ‘hybrid’ campus mode to transform learning in a ‘new normal’ era [ 27 , 28 ]. Another interesting finding was more than half of the students reporting that they needed more training on time management during the lockdown period.…”
Section: Discussionmentioning
confidence: 99%